2012
DOI: 10.1155/2012/582180
|View full text |Cite
|
Sign up to set email alerts
|

Low-Grade Esthesioneuroblastoma Presenting as SIADH: A Review of Atypical Manifestations

Abstract: Esthesioneuroblastoma (ENB) is a neuroendocrine tumor that typically manifests as advanced stage malignancy in the superior nasal cavity. The hallmark symptoms include nasal obstruction and epistaxis, which result from local tissue invasion. Atypical clinical features can also arise and must be considered when diagnosing and treating ENB. These can include origin in an ectopic location, unusual presenting symptoms, and associated paraneoplastic syndromes. The case described here reports a nasal cavity ENB with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 43 publications
2
17
0
2
Order By: Relevance
“…Other studies have reported secretion of adrenocorticotropic hormone from esthesioneuroblastomas . Syndrome of inappropriate antidiuretic hormone has also been reported in patients with esthesioneuroblastoma , …”
Section: Discussionmentioning
confidence: 89%
“…Other studies have reported secretion of adrenocorticotropic hormone from esthesioneuroblastomas . Syndrome of inappropriate antidiuretic hormone has also been reported in patients with esthesioneuroblastoma , …”
Section: Discussionmentioning
confidence: 89%
“…9 There are several reported cases of paraneoplastic syndromes related to vasopressin-or catecholamine-secreting esthesioneuroblastomas. 30,31 The majority of cases exhibit indolent growth; hence, symptoms may have been present for a prolonged period. Therefore, it is not surprising that incidental diagnosis on radiological investigation is often the initial presentation, as was the case with two patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported secretion of adrenocorticotropic hormone (ACTH) from esthesioneuroblastomas (17)(18)(19)(20)(21)(22)(23)(24) . Syndrome of inappropriate antidiuretic hormone (SIADH) has also been reported in patients with esthesioneuroblastoma (9,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) .…”
Section: Discussionmentioning
confidence: 99%